Genetic and phenotypic parameters of milk production traits in Jamunapari goats - Prajapati, Brijesh Kumar; Singh, Kishan Pal; Mandal, Ajoy; Rout, Promad KUMAR; Roy, Ramadhar (Indian Journal of Dairy Science, 2017)
The total 2244 lactations from 835 Jamunapari does maintained  (1985-2011)  were  analyzed 90-days, 140-days, total milk yield for this breed averaged 88.51±2.81, 132.40±4.95 and 156.01±5.06 lit., respectively. The average lactation length was 162.20±4.09 days. Significant differences among sires existed within the breed for all lactation traits. There were period of kidding had highly significant (P